The medicinal plants of Myanmar - Robert A. DeFilipps; Gary A. Krupnick (PhytoKeys, 2018)
A comprehensive compilation is provided of the medicinal plants of the Southeast Asian country of Myanmar (formerly Burma). This contribution, containing 123 families, 367 genera, and 472 species, was compiled from earlier treatments, monographs, books, and pamphlets, with some medicinal uses and preparations translated from Burmese to English. The entry for each species includes the Latin binomial, author(s), common Myanmar and English names, range, medicinal uses and preparations, and additional notes. Of the 472 species, 63 or 13% of them have been assessed for conservation status and are listed in the IUCN Red List of Threatened Species (IUCN 2017). Two species are listed as Extinct in the Wild, four as Threatened (two Endangered, two Vulnerable), two as Near Threatened, 48 Least Concerned, and seven Data Deficient. Botanic gardens worldwide hold 444 species (94%) within their living collections, while 28 species (6%) are not found any botanic garden. Preserving the traditional knowledge of Myanmar healers contributes to Target 13 of the Global Strategy for Plant Conservation.